Gendered cognitions: a socio-cognitive model of how gender affects entrepreneurial preferences - Wieland, Alice M., Markus, Kemmelmeier, Vishal K., Gupta; McKelvey, William (Entrepreneurship & Regional Development, 2019)
This research explores the social-cognitive factors which lead both women and men to pursue ventures consistent with their gendered social identity, therefore, reinforcing the gender gap in entrepreneurship. We measured the self-assessments of individuals presented with experimentally manipulated entrepreneurial opportunities that were either consistent or inconsistent with their self-reported gender. A theoretical model derived from Social Role Theory is presented and tested. It posits that a gender match (mismatch) with the entrepreneurial opportunity results in higher (lower) reported self-efficacy, anticipated social resources, and venture desirability and lower (higher) venture risk perceptions. The experimental data are tested in a sequential mediation SEM model. We find evidence that self-efficacy and anticipated social resources mediate the effect of gender congruency on perceived risk and venture desirability. The results provide insight into the insidious barriers that play a role in reproducing a gender gap in entrepreneurial outcomes by ‘nudging’ women into lower-return ventures in less lucrative industries.
_eprint: https://doi.org/10.1080/08985626.2018.1551787
Keywords: Entrepreneur; gender; gender gap; gender norms; gender role; opportunity evaluation; sex

Gendered cognitions: a socio-cognitive model of how gender affects entrepreneurial preferences - Wieland, Alice M.; Kemmelmeier, Markus; Gupta, Vishal K.; McKelvey, William (Understanding Women's Entrepreneurship in a Gendered Context, 2021)
Keywords: dept.mgt; peer-reviewed